The doMESTIC RISK Tool: Prioritising Home-Care Patients for Clinical Pharmacy Services with the Help of a Delphi Study - Carla Meyer-Massetti; Stefanie Lettieri-Amstutz; Daniela Rölli; Christoph R. Meier (Nursing Reports)
Background: Medication-related problems (MRPs) are common among home-care patients urgently needing improvement. Due to limited resources, patients with the greatest risk of MRPs should be prioritised for interventions. Objectives: We sought to develop a collaborative assessment tool for nurses and pharmacists to identify home-care patients at high risk of developing MRPs. Methods: Using Pubmed® for a first scoping literature review, we sought existing tools identifying patients at risk of MRPs or prioritising patients for clinical pharmacy services. Extracted items were prioritised in a first interprofessional Delphi round. Results from the first Delphi round were complemented by individual risk factors identified in a second scoping literature review and again submitted to the expert panel in a second Delphi round. Each item was rated for its relevance to identify home-care patients at risk of MRPs. The highest scoring factors were combined into an interprofessional assessment tool. Results: Literature review one yielded 19 risk tools and six lists containing potentially inappropriate medications. The 78 resulting risk factors were submitted to experts (five pharmacists, five physicians, five nurses) in Delphi round one. Since the identified tools did not fit the scope (interprofessional assessment in home care) entirely, the results of Delphi round one were complemented with individual risk factors identified in a second literature review, leading to 82 potential risk factors for Delphi round two. Experts decided on a 15-item tool for future pilot testing—the doMESTIC RISK tool. It incorporated diverse factors potentially influencing medication safety: demographic information, social context, diagnosis, specific medication and health care resources use. Conclusions: With expert feedback from a Delphi process, we developed a 15-item tool to help nurses and pharmacists jointly identify home-care patients at a high risk of MRPs. Validation of the doMESTIC RISK tool will be imperative to verify its value in clinical practice.